Transformative Islamic Education: The Role of Qur’anic Value Internalization in Building Santri’s Religious Character - Hishnuddin, As'ad; Jazilurrahman, Jazilurrahman (Journal of Educational Management Research, 2025)
This study aims to explore the implementation of Qur’anic values in shaping the religious character. The research employed a descriptive qualitative approach to investigate how Qur’anic principles are internalized through daily practices, role modeling, and institutional management. Data were collected through observation, interviews, and documentation involving teachers, students, and pesantren administrators. Findings reveal that the Qur’an serves not only as a textual source of knowledge but also as a behavioral guide actively embodied in the daily routines of santri. Religious character formation is facilitated through consistent activities such as communal prayers, Qur’an recitation, and ethical mentoring, supported by the exemplary behavior of teachers. Furthermore, the institutional management plays a strategic role in designing and maintaining an environment that integrates Qur’anic values into all aspects of pesantren life. The study concludes that the successful internalization of Qur’anic values results from a synergy of value-based education, modeling, and structured management. This model provides a transformative and holistic framework that addresses the contemporary crisis of moral and religious identity among Muslim youth, offering a replicable alternative for character education in formal settings.